2021
DOI: 10.3390/nu13051441
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Sarcopenia in Chinese Older Adults: Meta-Analysis and Meta-Regression

Abstract: Sarcopenia, with risk factors such as poor nutrition and physical inactivity, is becoming prevalent among the older population. The aims of this study were (i) to systematically review the existing data on sarcopenia prevalence in the older Chinese population, (ii) to generate pooled estimates of the sex-specific prevalence among different populations, and (iii) to identify the factors associated with the heterogeneity in the estimates across studies. A search was conducted in seven databases for studies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 76 publications
2
29
0
1
Order By: Relevance
“…The prevalence of sarcopenia was estimated in different countries and regions based on the diagnostic criteria. A meta‐analysis 8 suggested that the prevalence of sarcopenia among the elderly in Chinese communities was 12.9% in males and 11.2% in females and varied by diagnostic criteria and regions.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of sarcopenia was estimated in different countries and regions based on the diagnostic criteria. A meta‐analysis 8 suggested that the prevalence of sarcopenia among the elderly in Chinese communities was 12.9% in males and 11.2% in females and varied by diagnostic criteria and regions.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis by Chen et al also indicated that the odds of sarcopenia in Chinese men and women 80 years and older were two-to-three times higher than comparable people 60 to 70 years (females, OR= 3.28, 95% CI= 1.09–9.91; males, OR= 2.66, 95% CI= 1.28–5.50). 27 …”
Section: Discussionmentioning
confidence: 99%
“…These contradictory results may be attributable to the various restrictions associated with the diagnosis of sarcopenia and CVRF, the disparities between study participants, and the varying ethnic characteristics. In fact, it was showed that the prevalence of sarcopenia varies from 0 to 48%, depending on the background, parameters, and cutoffs of the study population (2,(36)(37)(38). Moreover, there are significant regional differences in the prevalence of CVD, reflecting variances in CVRF between nations and regions.…”
Section: Discussionmentioning
confidence: 99%